MASA INKUBASI PENYAKIT KARAT DAUN DAN TINGKAT KERUSAKAN PADA BIBIT PERUPUK (Lophopetalum multinervium) DI PERSEMAIAN PT. INHUTANI II MANDOR - Rabuansyah, Bandi; kandar, Is; Suryantini, Rosa (Universitas Tanjungpura, 2014)
This study aimed to determine the level of damage to seedlings perupuk caused by leaf rust disease and know the incubation time is needed leaf rust pathogen that infects seedlings perupuk and study the development of leaf rust disease symptoms on seedlings perupuk. Observation of the stricken plant was conducted using descriptive, of direct observation in the field and conducted an assessment of the extent of damage caused by the attack while the incubation time in the laboratory. The results showed that the leaf rust disease incubation time attacking seedlings perupuk (Lophopetalum multinevium) were 19 hours and the percentage of plants damaged by leaf rust disease were 71.22%. This was high and affects the quality of perupuk growth at the sites. While the average level of crop damage due to attack perupuk leaf rust disease on study sites were classified in the category that was equal to 44.26%. Keyword: Perupuk, attack rate, decay rate, incubation time.